Collaborative care for depression in older adults: How much is enough?. (December 2020) - Bonvoisin, Toby; Paton, Lewis W.; Hewitt, Catherine; McMillan, Dean; Gilbody, Simon; Tiffin, Paul A.
Abstract: Collaborative care in primary care has been shown to be effective for subthreshold depression in older adults in the 'CASPER' trial. However, to understand the impact of adherence, and to explore the minimum effective dose of collaborative care, we reanalysed the trial data using a complier average causal effect (CACE) analysis. Data were available for 705 participants, 519 with 12-month PHQ-9 scores. 'Compliance' could be observed for participants in the intervention group. Latent complier status in the control group was estimated. Completion of five or more sessions of care was defined as 'compliance'. Sensitivity analyses, using alternative cut-offs of two to eight sessions, assessed the impact of changing the definition of 'compliance'. Compliers in the intervention group had lower PHQ-9 scores at 12-month follow up than assumed compliers in the control group (1.75 lower, 95% confidence interval 0.29 to 3.21, p = 0.02), a greater effect than originally reported. Sensitivity analyses confirmed statistically significant differences between the intervention and control groups in those attending five or more sessions. We conclude that collaborative care is causally effective in reducing subthreshold depressive symptoms in older people who adhere to treatment. Our findings suggest the minimum effective dose is five sessions. Highlights: We estimate the causal effect of collaborative care on depression in older people. The effect size was a reduction in PHQ-9 points of 1.75 points. The 'minimally effective dose' of the intervention was five sessions. Further sessions added little additional symptomatic benefit.